SOCIAL CONFLICTS FOUND IN CHARLES DICKENS’ GREAT EXPECTATIONS - Ali Fauzi (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2017)
Literature is the expression of life in the works of beauty, truth, and cannot be separated from feeling, thought, or any activities as part of life. By literature, one can express his knowledge and get entertainment because literature is also defined as simply another way one can experience the world around him through his imagination. Meanwhile, novel as a genre of literature, is a reflection of reality the author writes based on his view. The novelist expresses ideas, or values which the readers can accept. In this research report, the researcher analyzes the novel “Great Expectations” to know better about the conflict happening in it mainly social conflict. It is about sad love and wonderful story of a boy named Pip whose parents died and who was brought up by his elder sister, Mrs. Joe Gargery. He loves a girl named Estella who always disdains him because he is a common and coarse boy. For this, he is eager to be a gentleman and wants to get her love. He has fortune because an escaped convict whom he helped when he was a child by giving some food and a file. The escaped convict whom later known as Provis pays Pip’s study in London and becomes a gentleman. That is why, he chooses the title “The Analysis of Social Conflicts in Charles Dickens’ Great Expectations”. This research is aimed at finding social conflicts undergone by Pip, Miss. Havisham, Provis and Orlick. Therefore, he formulates statement of the problems 1) What are social conflict undergone by Pip? 2) What are social conflict undergone by Miss. Havisham?, 3) What are Social conflict undergone by Provis? And 4) What are social conflict undergone by Orlick?. The Objectives of this research are: 1) to describe the social conflict undergone by Pip, 2) to describe the social conflict undergone by Miss. Havisham, 3) to describe the social conflict undergone by Provis and 4) to describe the social conflict undergone by Orlick. The researcher in discussing this problems uses many quotations taken from the Novel Great Expectations, and many references. They are taken in chapter II in form of Review of Related Literature. It looks that this research is Qualitative research by using descriptive text analysis. He uses Phenomenological approach as the basis of discussion. The object is the social conflict undergone by four main characters and the subject is the novel Great Expectations. After being analyzed, he finds that Pip undergoes social conflict with Estella, Mrs. Joe Gargery, Herbert, Orlick, Bentle Drummle and Miss. Havisham. Miss. Havisham experiences social conflict with Estella, Campeyson, and her relatives. Provis has social conflict with Compeyson, Orlick has social conflict with Mrs. Joe and Biddy. In fact, if it is examined closely, the conflicts happen around the problems of love either love relationship between Pip and Estella, Estella and Drummle, Compeyson and Miss. Havisham and Orlick with Biddy.